RANCANG BANGUN MESIN PENCACAH RUMPUT PAKAN TERNAK - Widyarini Widyarini; Sandi Yudha B Zaki; Tuti Alawiyah; Catur A.N. (Smart Education, 2026)
Abstract: Meeting the forage requirements of ruminant livestock demands an effective grass‑chopping process to ensure that feed is easier to consume, enhances digestive efficiency, and reduces the daily workload of farmers. In practice, however, grass chopping is still frequently performed manually, resulting in inconsistent particle sizes, high physical exertion, and significant delays in feed preparation. This study aims to design and develop a grass‑chopping machine that operates efficiently, safely, and is easy for small‑ to medium‑scale farmers to use. The design process involved identifying user needs, developing mechanical components, performing structural strength calculations, fabricating the frame and chopping chamber, and conducting machine performance tests. The results indicate that the developed machine can achieve a chopping capacity of 81 kg/hour at a blade rotational speed of 18,000 rpm, producing more uniform feed particles than manual methods. The incorporation of six straight blades on the rotating shaft effectively enhances the homogeneity of the chopped output while maintaining stable operational performance. Overall, the grass‑chopping machine designed in this study has proven capable of improving work efficiency, reducing the physical burden on farmers, and producing feed sizes better suited to livestock nutritional needs. Keywords: Grass Chopping, Livestock Feed, Design and Development Abstrak: Pemenuhan kebutuhan pakan hijauan bagi ternak ruminansia memerlukan proses pencacahan rumput yang efektif agar pakan lebih mudah dikonsumsi, meningkatkan efisiensi pencernaan, serta menghemat waktu kerja peternak. Pada praktiknya, pencacahan rumput masih banyak dilakukan secara manual sehingga menghasilkan potongan yang tidak seragam, memerlukan tenaga besar, dan memperlambat proses penyediaan pakan harian. Penelitian ini bertujuan merancang dan membangun sebuah mesin pencacah rumput pakan ternak yang mampu bekerja secara efisien, aman, dan mudah dioperasikan oleh peternak skala kecil hingga menengah. Perancangan dilakukan melalui tahap identifikasi kebutuhan, desain komponen mekanis, perhitungan kekuatan struktur, pembuatan rangka dan ruang pencacah, serta pengujian performa mesin. Hasil pengujian menunjukkan bahwa mesin yang dikembangkan mampu mencapai kapasitas pencacahan 81 kg/jam pada putaran pisau 18.000 rpm, dengan kualitas cacahan yang lebih seragam dibandingkan metode manual. Penggunaan enam pisau lurus pada poros berputar terbukti meningkatkan homogenitas hasil potongan serta menjaga stabilitas kerja mesin. Dengan demikian, mesin pencacah rumput yang dirancang pada penelitian ini terbukti mampu meningkatkan efisiensi waktu kerja, mengurangi beban fisik peternak, serta menyediakan potongan pakan yang lebih sesuai kebutuhan ternak. Kata Kunci: Pencacah Rumput, Pakan Ternak, Rancang Bangun